Plan de negocio, con proyección internacional, para la comercialización de servicios de educación superior virtual (2019)
The present monograph pretends to raise the viability of a business plan in the education sector, taking as a starting point the digital transformation, the accelerated movement of the market and the possibility of sell online product in the country and with a strong international potential. The sustenance of its feasibility will be based on surveys that show the type of audience to which the product will be directed and its sociodemographic characteristics, which will allow the correct orientation of the factors that influence its purchase and sale.